Beneficial Ownership in Tax Treaties: Judicial Interpretation and the Case for Clarity - Li, Jinyan (Tax polymath: a life in international taxation : essays in honour of John F. Avery Jones, 2010)
This book comprises a selection of papers presented at a conference in honour of John Avery Jones which was held on 22 and 23 April 2010 in London.Why this book?This book comprises a selection of papers presented at a conference in honour of John Avery Jones which was held on 22 and 23 April 2010 in London. The conference brought together experts in international and UK domestic taxation from around the world to celebrate Dr. Avery Jones's contribution to the fiscal arena to mark his 70th birthday and forthcoming retirement as Judge of the First and Upper Tier Tax Tribunals.The participators of the conference were drawn almost exclusively from three groups: the International Tax Group (ITG) of which Dr. Avery Jones was one of the founder members; the Advisory Group on the OECD Model; and UK tax academics. The papers reflect Dr. Avery Jones's many areas of interest, covering both international taxation and various aspects of UK domestic taxation. Many of the papers drew their inspiration from Dr. Avery Jones's academic writings or from his contribution as a tax judge.